REKONSTRUKSI PEMBELAJARAN PENCEMARAN TANAH BERBASIS STEM MELALUI INTEGRASI ARDUINO DALAM E-LKPD UNTUK MEMPERKUAT KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Purnami, Wiwin; Pratiwi Puspitawati, Rinie; Setyo Pratiwi, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growing demand for twenty-first-century competencies requires biology learning to facilitate students in developing critical thinking skills through authentic, technology-enhanced learning experiences. Nevertheless, classroom instruction remains predominantly teacher-centered, limiting students' opportunities to engage in scientific inquiry and evidence-based problem solving. This study aimed to develop and evaluate a STEM-based Electronic Student Worksheet (E-LKPD) integrated with Arduino and a deep learning approach to strengthen students' critical thinking skills in soil pollution learning. The study employed a Research and Development (R&D) method using the Four-D model, encompassing the stages of Define, Design, Develop, and Disseminate. The research involved 30 tenth-grade students at SMAN 1 Tarik. The developed product was evaluated based on its validity, practicality, and effectiveness through expert validation sheets, classroom implementation observations, student response questionnaires, and critical thinking assessments. The findings revealed that the developed E-LKPD achieved a high level of validity, demonstrated excellent practicality during implementation, and effectively enhanced students' critical thinking skills. Students' average achievement increased from a pretest score of 80 to a posttest score of 92, with an average N-Gain of 0.63, indicating a moderate improvement. The integration of Arduino within a STEM-oriented E-LKPD, supported by a deep learning approach, provides meaningful inquiry-based learning experiences that promote scientific reasoning and critical thinking. This study contributes to advancing technologyintegrated biology instruction by offering an innovative instructional framework for strengthening higher-order thinking skills in secondary education.